Extended‐field radiotherapy for locally advanced cervical cancer - Thamronganantasakul, Komsan (Cochrane Database Syst Rev, 2018)
BACKGROUND: The para‐aortic lymph nodes (located along the major vessels in the mid and upper abdomen) are a common place for disease recurrence after treatment for locally advanced cervical cancer. The para‐aortic area is not covered by standard pelvic radiotherapy fields and so treatment to the pelvis alone is inadequate for women at a high risk of occult cancer within para‐aortic lymph nodes. Extended‐field radiotherapy (RT) widens the pelvic RT field to include the para‐aortic lymph node area. Extended‐field RT may improve outcomes in women with locally advanced cervical cancer by treating occult disease in para‐aortic nodes not identified at pretreatment imaging. However, RT treatment of the para‐aortic area can cause severe adverse effects, so may increase harms. Studies of pelvic chemoradiotherapy (CRT) demonstrated improved survival rates compared to pelvic RT alone. CRT is now the standard of care in the treatment of locally advanced cervical cancer. Studies comparing pelvic RT alone (without concurrent chemotherapy) with extended‐field RT should therefore be viewed with caution, since they compare treatments against what is now substandard treatment (pelvic RT alone). This review should therefore be read with this in mind and comparisons with pelvic RT cannot be extrapolated to pelvic CRT. OBJECTIVES: To evaluate the effectiveness and toxicity of extended‐field radiotherapy in women undergoing first‐line treatment for locally advanced cervical cancer. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2018, Issue 7), MEDLINE via Ovid (1946 to August week 4, 2018), and Embase via Ovid (1980 to 2018, week 35). We checked registers of clinical trials, grey literature, conference reports, and citation lists of included studies to August 2018. SELECTION CRITERIA: We included randomised controlled trials (RCTs) evaluating the effectiveness and toxicity of extended‐field RT for locally advanced cervical cancer. DATA COLLECTION AND ANALYSIS: Two review authors independently selected potentially relevant RCTs, extracted data, assessed risk of bias, compared results, and made judgements on the quality and certainty of the evidence for each outcome. Any disagreements were resolved by discussion or consultation with a third review author. MAIN RESULTS: Five studies met the inclusion criteria. Three included studies compared extended‐field RT versus pelvic RT, one included study compared extended‐field RT with pelvic CRT, and one study compared extended‐field CRT versus pelvic CRT. Extended‐field radiotherapy versus pelvic radiotherapy alone  Compared to pelvic RT, extended‐field RT probably reduces the risk of death (hazard ratio (HR) 0.67, 95% confidence interval (CI) 0.48 to 0.94; 1 study; 337 participants; moderate‐certainty evidence) and para‐aortic lymph node recurrence (risk ratio (RR) 0.36, 95% CI 0.18 to 0.70; 2 studies; 477 participants; moderate‐certainty evidence), although there may or may not have been improvement in the risk of disease progression (HR 0.92, 95% CI 0.69 to 1.22; 1 study; 337 participants; moderate‐certainty evidence) and severe adverse events (RR 1.05, 95% CI 0.79 to 1.41; 2 studies; 776 participants; moderate‐certainty evidence). Extended‐field radiotherapy versus pelvic chemoradiotherapy  In a comparison of extended‐field RT versus pelvic CRT, women given pelvic CRT probably had a lower risk of death (HR 0.50, 95% CI 0.39 to 0.64; 1 study; 389 participants; moderate‐certainty evidence) and disease progression (HR 0.52, 95% CI 0.37 to 0.72; 1 study; 389 participants; moderate‐certainty evidence). Participants given extended‐field RT may or may not have had a lower risk of para‐aortic lymph node recurrence (HR 0.44, 95% CI 0.20 to 0.99; 1 study; 389 participants; low‐certainty evidence) and acute severe adverse events (RR 0.05, 95% CI 0.02 to 0.11; 1 study; 388 participants; moderate‐certainty evidence). There were no clear differences in terms of late severe adverse events among the comparison groups (RR 1.06, 95% CI 0.69 to 1.62; 1 study; 386 participants; moderate‐certainty evidence). Extended‐field chemoradiotherapy versus pelvic chemoradiotherapy  Very low‐certainty evidence obtained from one small study (74 participants) showed that, compared to pelvic CRT, extended‐field CRT may or may not have reduced risk of death (HR 0.37, 95% CI 0.14 to 0.96) and disease progression (HR 0.25, 95% CI 0.07 to 0.87). There were no clear differences between the groups in the risks of para‐aortic lymph node recurrence (RR 0.19, 95% CI 0.02 to 1.54; very low‐certainty evidence) and severe adverse events (acute: RR 0.95, 95% CI 0.20 to 4.39; late: RR 0.95, 95% CI 0.06 to 14.59; very low‐certainty evidence). AUTHORS' CONCLUSIONS: Moderate‐certainty evidence shows that, compared with pelvic RT alone, extended‐field RT probably improves overall survival and reduces risk of para‐aortic lymph node recurrence. However, pelvic RT alone would now be considered substandard treatment, so this result cannot be extrapolated to modern standards of care. Low‐ to moderate‐certainty evidence suggests that pelvic CRT may increase overall and progression‐free survival compared to extended‐field RT, although there may or may not be a higher rate of para‐aortic recurrence and acute adverse events. Extended‐field CRT versus pelvic CRT may improve overall or progression‐free survival, but these findings should be interpreted with caution due to very low‐certainty evidence. High‐quality RCTs, comparing modern treatment techniques in CRT, are needed to more fully inform treatment for locally advanced cervical cancer without obvious para‐aortic node involvement.